2014
DOI: 10.1016/j.reseneeco.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Can a unilateral carbon tax reduce emissions elsewhere?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Table 1 presents the articles reviewed. (Gupta & Mason, 2016) (Bodansky & Rajamani, 2013) (Ventura, et al, 2015) (Stewart, et al, 2013) (Moncel & Asselt, 2012) (Otto, et al, 2014) (Marcucci & Turton, 2013) (Kriegler, et al, 2015) (Riahi, et al, 2015) (Arroyo-Currás, et al, 2015) (Briner & Prag, 2013) (Chaturvedi, 2015) (Glomsrød, et al, 2013) (Gilley & Kinsella, 2015) Carbon tax 10 (Strand, 2013) (Alton, et al, 2014) (Wang & Li, 2015) (Gale, et al, 2013) ) (Elliott & Fullerton, 2013) (Sundar, et al, 2016) (Brooks, 2015) (Pezzey & Jotzo, 2013) (Lamperti, et al, 2015) Emission trading, trade, carbon markets 10 (Perthuis & Trotignon, 2013) (Uddin & Holtedahl, 2013) (Anon., 2013) ) (Lutz, et al, 2013) (Rabe, 2016) (Stiglitz, 2015) (Cormier, 2013) (Erickson, et al, 2014) (Sreekanth, et al, 2014) Carbon tax and cap-and trade 5 (Goulder & Schein, 2013) (Lui, 2016) (Sewalk, 2013) (Repetto, 2013) Minilateralism 8 (Debaere, et al, 2014) (Falkner, 2015) (Hjerpe & Nasiritousi, 2015) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the articles reviewed. (Gupta & Mason, 2016) (Bodansky & Rajamani, 2013) (Ventura, et al, 2015) (Stewart, et al, 2013) (Moncel & Asselt, 2012) (Otto, et al, 2014) (Marcucci & Turton, 2013) (Kriegler, et al, 2015) (Riahi, et al, 2015) (Arroyo-Currás, et al, 2015) (Briner & Prag, 2013) (Chaturvedi, 2015) (Glomsrød, et al, 2013) (Gilley & Kinsella, 2015) Carbon tax 10 (Strand, 2013) (Alton, et al, 2014) (Wang & Li, 2015) (Gale, et al, 2013) ) (Elliott & Fullerton, 2013) (Sundar, et al, 2016) (Brooks, 2015) (Pezzey & Jotzo, 2013) (Lamperti, et al, 2015) Emission trading, trade, carbon markets 10 (Perthuis & Trotignon, 2013) (Uddin & Holtedahl, 2013) (Anon., 2013) ) (Lutz, et al, 2013) (Rabe, 2016) (Stiglitz, 2015) (Cormier, 2013) (Erickson, et al, 2014) (Sreekanth, et al, 2014) Carbon tax and cap-and trade 5 (Goulder & Schein, 2013) (Lui, 2016) (Sewalk, 2013) (Repetto, 2013) Minilateralism 8 (Debaere, et al, 2014) (Falkner, 2015) (Hjerpe & Nasiritousi, 2015) …”
Section: Resultsmentioning
confidence: 99%
“…They evaluated the effectiveness based on several dimensions such as sharing the political burden. Elliott & Fullerton (2013) completed another study in US and concluded that the carbon tax might be the best option. Subsequently Elliott & al concluded that carbon tax only in Annex1 countries would not be effective but the carbon tax should be adopted globally.…”
Section: Carbon Taxmentioning
confidence: 99%
“…As a result, demand and emissions in the policy inactive regions go up. Estimates of the size of this carbon leakage effect vary from 5 to over 30% of the reduction in policy active regions (Burniaux and Martins 2012;Böhringer et al 2017), but there are also extreme examples of negative leakage rates (Elliott and Fullerton 2014) and a leakage rate of 130% (Babiker 2005).…”
Section: Carbon Leakage and The Green Paradoxmentioning
confidence: 99%
“…3 Several other channels have been identi ed: the di usion of new green technologies can induce a negative leakage (Golombek and Hoel, 2004;Gerlagh and Kuik, 2007), subsequent changes of wealth can induce a positive or negative leakage (Elliott and Fullerton, 2013), and the change of the marginal environmental damage modi es the optimal emissions in other countries (see for instance the work on environmental coalitions by Carraro and Siniscalco, 1993;Barrett, 1994).…”
mentioning
confidence: 99%